2010
DOI: 10.1111/j.1460-9568.2010.07220.x
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐I stimulates neurogenesis in the hypothalamus of adult rats

Abstract: In the brain of adult rats neurogenesis persists in the subventricular zone of the lateral ventricles and in the dentate gyrus of the hippocampus. By contrast, low proliferative activity was observed in the hypothalamus. We report here that, after intracerebroventricular treatment with insulin-like growth factor I (IGF-I), cell proliferation significantly increased in both the periventricular and the parenchymal zones of the whole hypothalamus. Neurons, astrocytes, tanycytes, microglia and endothelial cells of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
166
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(182 citation statements)
references
References 46 publications
13
166
1
2
Order By: Relevance
“…Although recent studies have focused attention on b2-tanycytes as proliferating progenitors 22,23 , earlier studies suggested that a-tanycytes may harbour neural stem/progenitor potential in the adult 6,11 . To examine whether adult a-tanycytes possess neural stem/progenitor functions, we searched for an appropriate genetic means to label them.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although recent studies have focused attention on b2-tanycytes as proliferating progenitors 22,23 , earlier studies suggested that a-tanycytes may harbour neural stem/progenitor potential in the adult 6,11 . To examine whether adult a-tanycytes possess neural stem/progenitor functions, we searched for an appropriate genetic means to label them.…”
Section: Resultsmentioning
confidence: 99%
“…In the adult rat, fate-mapping experiments of the hypothalamic ventricular wall first showed that proliferating ependymal cells, including but not exclusively tanycytes, can give rise to progeny that migrate along tanycyte processes 11 . Additional studies in the adult rat revealed an enhanced proliferation of tanycytes in response to IGF-1 6 . In the mouse, lineage-tracing studies have demonstrated that a subset of b-tanycytes, the b2-tanycytes, can proliferate and are neurogenic, contributing new neurons to hypothalamic nuclei in the postnatal/juvenile period 22 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Birth of new neurons that integrate locally in functional circuits underlying hormone production and release has been observed in the hypothalamus in response to insulin-like growth factor 1 (IGF-1) administration, leading to the identification of a specific 'neurogenic niche' in the walls of the third ventricle [19], which will not be analysed in this paper. As mentioned, precursors in neurogenic areas derive from embryonic radial glial cells, whose proliferation and differentiation are tightly controlled by intercellular calcium waves.…”
Section: Introductionmentioning
confidence: 99%